Piltdown Mistification in View of the K. Popper Science Rationality and Sociological Reductionism of Edinburgh School - Abdank-Kozubski , Andrzej (Studia Ecologiae et Bioethicae, 2004)
Historically evidenced faulty scientific theories undoubtedly influenced the formation of particular concepts of science. The paleoanthropological case known as a discovery of Piltdown Human illustrates this statement. In this context, the persistent tendency for rescuing questioned hypotheses or theories is a characteristic feature of science. Despite natural expectations, it is just the feature that guarantees the correct development of science. The statement corresponds to the K. R. Popper concept of the rationality of science, as well as to some particular postulates of the Edinburgh School.